Continuity of medication information transfer and continuous medication supply during hospital-to-home transitions - nationwide surveys in hospital and community pharmacies after implementing new legal requirements in Germany - Klasing, Sophia; Dörje, Frank; Hilgarth, Heike; Metzger, Nadine; Richling, Ina; Seidling, Hanna M. (BMC Health Services Research, 2024)
Background: While successful information transfer and seamless medication supply are fundamental to medication safety during hospital-to-home transitions, disruptions are frequently reported. In Germany, new legal requirements came into force in 2017, strengthening medication lists and discharge summaries as preferred means of information transfer. In addition to previous regulations – such as dispensing medication at discharge by hospital pharmacies – hospital physicians were now allowed to issue discharge prescriptions to be supplied by community pharmacies. The aim of this survey study was to gain first nationwide insights into how these requirements are implemented and how they impact the continuity of medication information transfer and continuous medication supply. Methods: Two nationwide self-administered online surveys of all hospital and community pharmacies across Germany were developed and conducted from April 17th to June 30th, 2023. Results: Overall, 31.0% (n = 111) of all German hospital pharmacies and 4.5% (n = 811) of all community pharmacies participated. The majority of those hospital pharmacies reported that patients who were discharged were typically provided with discharge summaries (89.2%), medication lists (59.5%) and if needed, discharge prescriptions (67.6%) and/or required medication (67.6%). About every second community pharmacy (49.0%) indicated that up to half of the recently discharged patients who came to their pharmacy typically presented medication lists. 34.0% of the community pharmacies stated that they typically received a discharge summary from recently discharged patients at least once per week. About three in four community pharmacies (73.3%) indicated that most discharge prescriptions were dispensed in time. However, one-third (31.0%) estimated that half and more of the patients experienced gaps in medication supply. Community pharmacies reported challenges with the legal requirements – such as patients´ poor comprehensibility of medication lists, medication discrepancies, unmet formal requirements of discharge prescriptions, and poor accessibility of hospital staff in case of queries. In comparison, hospital pharmacies named technical issues, time/personnel resources, and deficits in patient knowledge of medication as difficulties. Conclusion: According to the pharmacies´ perceptions, it can be assumed that discontinuation in medication information transfer and lack of medication supply still occur today during hospital-to-home transitions, despite the new legal requirements. Further research is necessary to supplement these results by the perspectives of other healthcare professionals and patients in order to identify efficient strategies.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Continuity of patient care; Drug therapy; Health information exchange; Hospital-to-home transitions